2013
DOI: 10.2478/s11658-013-0106-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the unfolded protein response by microRNAs

Abstract: The unfolded protein response (UPR) is an adaptive response to the stress that is caused by an accumulation of misfolded proteins in the lumen of the endoplasmic reticulum (ER). It is an important component of cellular homeostasis. During ER stress, the UPR increases the protein-folding capacity of the endoplasmic reticulum to relieve the stress. Failure to recover leads to apoptosis. Specific cellular mechanisms are required for the cellular recovery phase after UPR activation. Using bioinformatics tools, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 112 publications
0
45
2
Order By: Relevance
“…Using the dedicated bioinformatical approach as described in Bartoszewska et al (15), we searched for miRNAs with potential base-pair complementarities to conserved sequences in the XBP1 mRNA 39-UTR. This analysis predicted a target site for miR-34c-5p in the XBP1 39-UTR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the dedicated bioinformatical approach as described in Bartoszewska et al (15), we searched for miRNAs with potential base-pair complementarities to conserved sequences in the XBP1 mRNA 39-UTR. This analysis predicted a target site for miR-34c-5p in the XBP1 39-UTR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although ER stress-induced miRNAs contribute to both recovery and the apoptotic arms of UPR pathway and thus balance cell fate (15)(16)(17), the detailed mechanisms of their actions on multiple components of UPR are less clear. To date, the ER stress-inducible miRNAs were mainly considered as factors that reduce ER protein load (28,45) and thus contribute to cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used TaqManOne-Step RT-PCR Master MixReagents (Applied Biosystems) as described previously (Bartoszewska et al, 2013; Bartoszewski et al, 2011; Bartoszewski et al, 2014) using the manufacturer’s protocol. The relative expressions were calculated using the comparative relative standard curve method (Larionov et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs regulate protein expression by degrading target mRNA or inhibiting translation, resulting in complementary matching between miRNAs and specific sites in target mRNAs (42), correlate with human disease and have a potential as therapeutic targets (43)(44)(45). Emerging evidence suggests miRNAs control the balance of pro-survival and pro-apoptotic signals by acting at different steps in each arm of the pathway to regulate ER stress (46). To identify the possible mechanisms, the expression of miR-34a was examined by RT-qPCR and results showed that miR-34a was markedly downregulated in TM-exposed chondrocytes treated with DHJSD or PBA.…”
Section: Discussionmentioning
confidence: 99%